All-inorganic quantum-dot light-emitting diodes based on perovskite emitters with low turn-on voltage and high humidity stability. Issue 18 (25th April 2017) - Shan, Qingsong; Li, Jianhai; Song, Jizhong; Zou, Yousheng; Xu, Leimeng; Xue, Jie; Dong, Yuhui; Huo, Chengxue; Chen, Jiawei; Han, Boning; Zeng, Haibo
Abstract : We present the all-inorganic QLEDs, including inorganic perovskite emitters (CsPbBr3 ) and inorganic charge transport layers (CTLs), with emphasis on the significantly improved device stability and low turn-on voltage. Abstract : Recently, both light-to-electricity and electricity-to-light conversion efficiencies of perovskite achieved a breakthrough, e.g. 22.1% for solar cells and 11.7% for light-emitting diodes (LEDs), so the next fatal problem towards practical application, the device stability, became the key issue in this field. Here, we report all-inorganic LEDs including inorganic perovskite emitters (CsPbBr3 ) and inorganic charge transport layers (CTLs), with an emphasis on the significantly improved device stability. The quantum dot LEDs (QLEDs) were fabricated according to ITO/NiO/CsPbBr3 QDs/ZnO/Al device configuration. On the one hand, the all-inorganic LED lifetime under 65% humidity corresponding to a 70% electroluminescence (EL) conservation rate can be improved up to 3.5 times when compared with LEDs adopting conventional organic CTLs due to the intrinsic chemical stability of these inorganic CTLs and their less hydrophilic surfaces. Furthermore, as a surprise, the bare all-inorganic LED without encapsulation can work in water for about 20 seconds, which is over 10 times more sustainable than the organic–inorganic LED, which proves the excellent water-isolation ability. On the other hand, the all-inorganic QLEDs show the lowest turn-on voltage of 2.4 V among all the reported CsPbBr3 QLEDs because the inorganic CTLs possess well-matched energy band alignments with CsPbBr3, and hence result in efficient carrier injection. This work paves the way to constructing all-inorganic devices for stable perovskite photovoltaic and light-emitting devices.